Efficient and non‐toxic gene delivery by anionic lipoplexes based on polyprenyl ammonium salts and their effects on cell physiology. (November 2016) - Rak, Monika; Ochałek, Anna; Bielecka, Ewa; Latasiewicz, Joanna; Gawarecka, Katarzyna; Sroka, Jolanta; Czyż, Jarosław; Piwowarczyk, Katarzyna; Masnyk, Marek; Chmielewski, Marek; Chojnacki, Tadeusz; Swiezewska, Ewa; et al.
Abstract: Background: One of the major challenges limiting the development of gene therapy is an absence of efficient and safe gene carriers. Among the nonviral gene delivery methods, lipofection is considered as one of the most promising. In the present study, a set of cationic polyprenyl derivatives [trimethylpolyprenylammonium iodides (PTAI)] with different lengths of polyprenyl chains (from 7, 8 and 11 to 15 isoprene units) was suggested as a component of efficient DNA vehicles. Methods: Optimization studies were conducted for PTAI in combination with co‐lipid dioleoylphosphatidylethanolamine on DU145 human prostate cancer cells using: size and zeta potential measurements, confocal microscopy, the fluorescein diacetate/ethidium bromide test, cell counting, time‐lapse monitoring of cell movement, gap junctional intercellular coupling analysis, antimicrobial activity assay and a red blood cell hemolysis test. Results: The results obtained show that the lipofecting activity of PTAI allows effective transfection of plasmid DNA complexed in negatively‐charged lipoplexes of 200–500 nm size into cells without significant side effects on cell physiology (viability, proliferation, morphology, migration and gap junctional intercellular coupling). Moreover, PTAI‐based vehicles exhibit a potent bactericidal activity against Staphylococcus aureus and Escherichia coli . The developed anionic lipoplexes are safe towards human red blood cell membranes, which are not disrupted in their presence. Conclusions: The developed carriers constitute a group of promising lipofecting agents of a new type that can be utilized as effective lipofecting agents in vitro and they are also an encouraging basis for in vivo applications.